EXAMINING THE RELATIONSHIP BETWEEN RISKS AND EFFICIENCY OF ISLAMIC BANKS IN MALAYSIA (International Journal of Islamic Business, 2016)
This paper aims to examine the efficiency level of Islamic banks in Malaysia and their relation to credit risk, liquidity risk and operational risk. Twelve Islamic banks were chosen as samples for this study which were taken by the availability of data, through each banks’ annual report from 2008 to 2013. This study was carried by applying the Data Envelopment Analysis (DEA) and Multiple Regression Analysis to achieve its objectives. The finding shows that Islamic banks in Malaysia exhibited a total of 77.1% of overall efficiency of technical (OTE), 83.1% of Pure Technical Efficiency (PTE) and 92.6% of Scale Efficiency (SE). Despite the global financial crisis that occured during the middle year of 2007 to the end of 2009 which slightly affected Asian countries such as Malaysia, nevertheless, Islamic banks seem to be more robust during the crisis than conventional banks. This is because of its basic nature which prohibited interest payments (riba) in all transactions. This study shows that credit risk has a negative significant relationship with efficiency of Islamic banks, while liquidity was found to be positive related to efficiency of Islamic banks. This study also found that the size of the bank has positive significant relationship to efficiency. Finding from this study give contribution to the policy makers and regulators as well as to the managers of Islamic banks by providing empirical evidence on the performance of the Islamic banks in Malaysia towards the efficiency level and risks relationship.